A Quantitative Approach to Book-Printing in Sweden and Finland, 1640–1828. Issue 1 (2nd January 2019) - Tolonen, Mikko; Lahti, Leo; Roivainen, Hege; Marjanen, Jani
Abstract: Several cities in Sweden have been providing book-printing facilities since the 1640s. In our quantitative and explorative analysis of library catalogs from the National Library of Sweden and the National Library of Finland we identify the general trends in publishing, how book-printing has been affected by political events, and how printing developed at different paces in different parts of the realm. We have developed a new method for analyzing the totality of publishing through extensive data harmonization and comprehensive statistical analysis, and by treating library catalogs not as an endpoint of bibliographic research but as an inherently rich source of information. This facilitated the quantitative assessment of printing in the Swedish realm based on the metadata contained in library catalogs. Our data-driven approach to the transformation of public discourse demonstrates that whereas the amount of printed material grew steadily, political ruptures affected the development of printing. We also suggest that the culture of books and printing is best understood through the dynamics of competing intellectual hubs consisting of the university cities and the political center in Stockholm. This perspective further challenges the dominant, nationally delineated approach in book history.